EVALUATION OF EMERGENCY RESPONSE SYSTEM AT TIMERGARA TEACHING HOSPITAL, LOWER DIR, KHYBER PAKHTUNKHWA – A CROSS SECTIONAL STUDY (The Research of Medical Science Review, 2024)
The aim of study was to investigate emergency response system at Timergara Hospital and to determine disaster preparedness protocols.It was cross sectional study in which FGD guide was used as data collection tool. The study was conducted with the Medical Staff working at the Emergency department and Hospital Administrators working at Timergara Teaching Hospital. A sample size 91 was taken . Analysis was done by SPSS and thematic analysis.The analysis of the medical staff distribution, emergency training, and emergency measures at Timergara Hospital, complemented by the thematic insights from the focused group discussion (FGD), reveals several strengths and areas for improvement in the hospital's emergency response system.